Monitoring costs of multinational companies: an agency theory perspective - Mustapha, Mazlina (Faculty of Business and Accountancy, University of Malaya, 2014)
This paper investigates the agency costs of multinational companies (MNCs) in relation to agency theory, in the Malaysian business environment. Using the data of 235 MNCs, this study explores their demand for monitoring costs and these companies' preferences between the monitoring costs components. The result indicates that MNCs incur significantly higher monitoring costs compared to domestic companies. However, the relationship between these companies and their preference between the components of the monitoring mechanisms, that is between directorship and auditing as their monitoring mechanism, is not significant. When the auditing components are further investigated, it reveals that MNCs incur more external audit costs compared to internal audit costs.